Panepiphanal World : James Joyce's Epiphanies - MacDuff, Sangam; MacDuff, Sangam (Book collections on Project MUSE., 2020)
"This book is the first in-depth study of the forty short texts James Joyce called "epiphanies." Sangam MacDuff argues that the epiphanies are an important point of origin for Joyce's entire body of work, showing how they shaped the structure, style, and language of his later writings"